CXCL13 CSF level inversely correlates with duration of disease in primary progressive multiple sclerosis - Losy, Jacek; Iwanowski, Piotr; Kaufman, Elżbieta; Wójcicka, Marlena (Journal of Medical Science, 2016)
Chemokines are important factors in the immunopathogenesis of multiple sclerosis. The objective of the study was to examine the CSF and serum levels of CXCL13 and CCL5 chemokines in primary progressive MS, compare results with relapsing remitting MS and control group with other noninflammatory neurological disorders. The levels of chemokines was measured by ELISA method. The CXCL13 CSF levels in PP and RR MS were higher in comparison with control group, without significant differences between these podgroups. Additionally CXCL13 level in PP MS inversely correlated with duration of the disease. CCL5 CSF level was also significantly higher in PP MS in comparison with control group. The results demonstrate involvement of CXCL13 and CCL5 chemokines in the immunopathogenetic mechanisms of primary progressive MS.
Keywords: chemokines; multiple sclerosis; immunopathology